2016
DOI: 10.1002/bmc.3711
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism studies on prim‐O‐glucosylcimifugin and cimifugin in human liver microsomes by ultra‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry

Abstract: Prim-O-glucosylcimifugin (PGCN) and cimifugin (CN) are major constituents of Radix Saposhnikoviae that have antipyretic, analgesic and anti-inflammatory pharmacological activities. However, there were few reports with respect to the metabolism of PGCN and CN in vitro. In this paper, we describe a strategy using ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) for fast analysis of the metabolic profile of PGCN and CN in human liver microsomes. In total, five ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Multivariate statistical analysis allowed metabolites of SDD to be identified faster and allowed us to visually recognize key metabolites, even those with lower concentrations. Using this method, more metabolites were identified compared with previous studies on metabolism of SDD or monomer compounds in SDD (Li et al, ; Jia et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate statistical analysis allowed metabolites of SDD to be identified faster and allowed us to visually recognize key metabolites, even those with lower concentrations. Using this method, more metabolites were identified compared with previous studies on metabolism of SDD or monomer compounds in SDD (Li et al, ; Jia et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…So far, there have been few reports on the metabolism of orally administered Saposhnikovia divaricate decoction (SDD). An existing study on the in vivo metabolism of compounds identified in SDD was restricted to only two main compounds (Jia et al, ). Understanding the absorbed constituents and metabolites of TCMs is crucial for the determination of their pharmacologically active substances.…”
Section: Introductionmentioning
confidence: 99%
“…The third step was to identify the chemical structure of metabolites based on the accurate mass measurement, relevant biotransformation knowledge, and reported fragmentation patterns of parent drug and MS/MS spectrum of metabolites. Finally, metabolites were obtained by comparing the extracted ion chromatograms and base peak chromatograms of the sample group with those of the blank group using Peakview software 2.2 . Furthermore, Clog P that can avoid many isomers usually being identified as a single compound was calculated by the program Chemdraw Ultra 14.0.…”
Section: Resultsmentioning
confidence: 99%
“…After losing two CH 3 groups, the fragment ion at m / z 273.1104 produced fragment ion at m / z 243.0633. Fragment ion at m / z 273.1103 yielded other fragment ions at m / z 231.0635, 205.0481, 189.0540 through dropping continuously C 3 H 6 , C 2 H 2 , and O . And the fragment ion at m / z 231.0635 get product ion at m / z 217.0422 via losing CH 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation